Examining the Government's Efforts to Curb Abandoned Land - Utomo, Setiyo (Arena Hukum, 2024)
Controlling land indicated as abandoned is part of aligning agrarian reform goals. Effective land management will ensure land is used according to its intended purposes, including the right to cultivate. This study aims to describe and provide an overview of land classified as abandoned, focusing on land with cultivation rights granted and offers recommendations for respecting and protecting the community’s rights to the land they own. This study employs a normative juridical approach by comparing cases and statutory frameworks. The findings reveal various factors contributing to land abandonment and the government’s efforts to address this issue. Established norms should guide legal actions to achieve certainty and justice in land use. Implementing legal measures is part of harmonising existing regulations with societal realities, as outlined in paragraph 4 of the 1945 Constitution of the Republic of Indonesia, which mandates that the government protect the entire nation and promote the well-being of all citizens.